Funerary practices in the Czech Republic - Nešporová, Olga (Bingley, U.K. : Emerald Publishing Limited, 2020)
Exploring the traditions, customs and contemporary legal framework of Czech funerary practices, this book analyses and interprets the high cremation rate, predominance of secular funerals and increasing popularity of cremation with no funeral ceremony against the background of the country's historical development.
Prelims -- 1 Introduction -- 2 History -- 3 Demographic and legal frameworks -- 4 Crematoria and cremation -- 5 The funeral and the funeral ceremony -- 6 Funeral costs -- 7 Burial sites -- 8 Commemoration -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Funeral rites and ceremonies -- Czech Republic; Cremation -- Czech Republic; Burial laws -- Czech Republic; Religion, Christian Rituals & Practice, Sacraments; Funeral services